«ЕЗДА В ОСТРОВ ЛЮБВИ» И ЛИТЕРАТУРНАЯ ПОЗИЦИЯ В.К.ТРЕДИАКОВСКОГО В ПЕРВОЙ ПОЛОВИНЕ 1730-Х ГОДОВ: Ezda v Ostrov Ljubvi and literary position of V. K. Tretyakovsky in the first half of the 1830s - Bucharkin, Piotr (Prace Polonistyczne, 2019)
The article considers the literary position of V.K. Trediakovsky in 1730–1735, which centered upon the idea of the sufficiency of Westernization gained by Russian literature in the epoch of Peter the Great. Initially, Trediakovsky held that the literary movement should promote the development of existing fundamentals rather than revolutionizing renovation. However, after having successfully incarnated his ideas in concrete artistic texts, namely – Ezda v Ostrov Ljubvi (A Journey to the Island of Love) and Pindaric ode Oda Torzhestvennaya o Sdache goroda Gdanska (Triumphant Ode on the Surrender of the City of Gdansk) – Trediakovsky drastically changed his literary position and started to demand that artistic discourse should be radically changed.